Building strategic scenarios during Covid-19 lockdown: Insights from a university-class remote simulation - Santoro, Stefania; Stufano Melone, Maria Rosaria; Camarda, Domenico (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Since early spring 2020, the outbreak of the COVID-19 in Italy caused schools and universities to lock and shift from traditional face-to-face classroom education to online education. In the academic field of spatial planning, online education and examples of on-line participatory process (e.g. e-planning, e-governance, etc.) are traditionally not very frequent. Through the application of an on-line participatory process to build a future vision of Bari (Apulia Region), this study explores elements related to the behavior of the knowledge agents involved in the process and compares them with the application of previous face-to-face classroom examples. The results obtained allow to collect some suggestions not only on the performance of the application in two different times, but also on the potential elements of difference to be associated to the temporal and psychological context related to the diffusion of COVID-19. Since these conditions are clearly exceptional and practically (hopefully) unrepeatable, the results seem to show a mixed perspective of effectiveness for the use of online education to build a future vision of a city.